Extraction of frequency-dependent parameters of passive superconductor structures using the finite-difference time-domain method at sub-terahertz frequencies - Meyer, Kobus (Stellenbosch : Stellenbosch University, 2024)
Thesis (MEng)--Stellenbosch University, 2024.